PENGARUH KEBUTUHAN MOTIVASI EKSTRINSIK, DUKUNGAN REKAN KERJA DAN RELIGIUSITAS TERHADAP KEPUASAN KERJA PADA PEGAWAI KANTOR KEMENTERIAN AGAMA KABUPATEN PADANG PARIAMAN - Surmi Damila; Evi Susanti Tasri (Ensiklopedia of Journal, 2022)
This study aims to see the effect of Extrinsic Motivation, Co-worker Support and Religion on Job Satisfaction of Employees of the Ministry of Religion, Padang Pariaman Regency. The method used in this research is quantitative research with a descriptive approach. The population in this study were all employees of the Office of the Ministry of Religion, Pada Regency padang Pariaman as many as 62 people using a sampling technique. This study uses multiple linear regression test. The results of this study indicate that extrinsic motivation, co-worker support and religiosity have a positive and significant influence together on job satisfaction of employees of the Ministry of Religion Office of Padang Pariaman Regency.